PENGADAAN TANAH UNTUK PERKEBUNAN KELAPA SAWIT DALAM PERSPEKTIF LINGKUNGAN HIDUP - H Joni (University of Merdeka Malang, 2015)
Land procurement is every activity to get land by movement right of land or by transfer of right of land bycompensation to the deserved one. In land procurement process for palm oil garden, first thing to do is to observethe available land, whether is State land, Land of Right or Land Right Management. Oil Palms Corporation is theone who get land is has to observe the land claim rules in which provided by National Land Law, which is thelocation and available land status. In term land procurement, sometimes it will be facing problem. Indigenouspeople is still to release their right of land because they are already emotionally binding with the land. Becausethey are certain that the land has power so it can not be released. Besides of that, all of people activities is centeredon the land, such as farming, gardening, indigenous or religious activity. The point is, land is unseparatable partfrom all daily activities, not only land has emotional bind (religious-magic) with the people, but also with waterand forest. Because of that land procurement for oil palm has to observe land rights that already attached to theland that possessed by indigenous people. After land possession is appropriate by the Location Permit, Corporationcan propose Right of Business to National Land Institution with terms applied.